Zero-Valent Iron Nanoparticles in Soil and Groundwater Remediation; Applications, Toxicity, Fate and Transport Mechanisms - Demir, Sultan Akarcay; Demir, Ahmet; Bilgili, Mehmet Sinan (Mehmet Sinan Bilgili, 2022)
During the last two decades application of nanomaterials to eliminate contamination has been increased. Especially in-situ remediation of soils and groundwaters by nanomaterials has been gained growing attention. In this paper a review work has been done based on some of remarkable studies of the field. Nano-scale zero valent iron had been choosed as it is the most frequently used nano material for remediation of contaminated soil and groundwater. The objective of this study is to evaluate efficiency of nano-scale zero valent iron along with toxicity of nZVI, its' effect on the soil and groundwater geochemical properties and fate and transport mechanisms. Figuring out these challenges all together is a very important in order to categorize nZVI as environmentally safe and effective material. As a result, nZVI seemed to provide high removal efficiencies (up to 82%) for both organic and inorganic pollutants, toxicity mainly caused by ROS (reactive oxygen species) in presence of nZVI, and those nanoparticles have impact on the media's pH and ORP (oxidation reduction potential). nZVI particles usually get immobile in the media and transform into iron minerals eventually.
Keywords: Nanotechnology; Iron nanoparticles; Zero-valent iron; Soil remediation; Groundwater remediation; NANO; TRANSFORMATION; OXIDE; NZVI; Engineering; Environmental Sciences & Ecology